Evaluating the Effect of Roadway and Development Factors on the Rural Road Safety Risk Index - Shahriar Afandizadeh; Shahab Hassanpour (Advances in Civil Engineering)
As roadway and development factors are identified as the most effective factors contributing to road traffic accidents, investigating these factors could lead to reducing the accident frequency rate. However, previous works focused on investigating the effect of roadway factors on the accident frequency rate using statistical analysis. The present study aimed to evaluate the effect of roadway and development factors on the accident frequency rate using ANOVA and Chi-square tests on a rural road. Secondly, it aimed to develop a rural road safety risk index based on K-means clustering and Gaussian models. The findings indicated that the operating speed and the differences between posted speed limits and the operating speed are the pivotal influencing factors on the accident frequency rate. Moreover, clustering analysis of the roadway and development factors on the two-lane, two-way road of Borujerd-Khorramabad indicated six clusters which were identified as highly, relatively highly, moderately, relatively lowly, lowly risky, and not risky (safe) clusters. Regarding clusters, the accident frequency rate increased by decreasing the difference between the posted speed limits and the operating speed from the safe cluster. In addition, the risky index model based on the Gaussian model showed that the average reducing factor of accident frequency rate reached 0.99 by increasing per km/hr in the difference between the posted speed limits and the operating speed among low risky and safe clusters, while it was equal to 1.17 in risky and unsafe clusters. The comparison of the clusters revealed that accident occurrence probability in risky clusters was more than the ones in low risky or safe clusters. Therefore, the maximum and minimum values of the safety risk index were observed in the sixth and the third clusters, respectively.